Arachidonate 5-Lipoxygenase Gene Variants Affect Response to Fish Oil Supplementation by Healthy African Americans(2) - Armstrong, Patrice (American Society for Nutrition, 2012)
Arachidonate 5-lipoxygenase (ALOX5) gene variants that are common in people of African ancestry are associated with a differential cardiovascular disease (CVD) risk that may be ameliorated by intake of (n-3) PUFA, such as EPA or DHA. We conducted a double-masked, placebo (PL)-controlled trial of fish oil (FO) supplements to determine if changes in erythrocyte (n-3) PUFA composition, heart rate, blood pressure, and plasma lipid and lipoprotein concentrations are modified by genotype. Participants received 5 g/d FO (2 g EPA, 1 g DHA) or 5 g/d corn/soy oil (PL). A total of 116 healthy adults of African ancestry with selected genotypes (genotypes = “dd,” “d5,” and “55” with “d” representing the deletion of 1 or 2 Sp1 binding sites in the ALOX5 promoter and “5” indicating the common allele with 5 sites) were enrolled and 98 completed the study. FO caused significant increases (relative to PL) in erythrocyte EPA, DHA, and total (n-3) PUFA and a decrease in the (n-6) PUFA:(n-3) PUFA ratio in the low-CVD risk “d5” and “55” genotypes but not in the high-risk “dd” genotype. Similarly, HDL particle concentration decreased with FO relative to PL in the “d5” and “55” but not “dd” genotypes. The plasma TG concentration decreased significantly with FO relative to PL in the “d5” but not “dd” and “55” genotypes. No changes were seen in LDL particle or cholesterol concentrations, heart rate, or blood pressure. These findings indicate that the efficacy of FO supplements vary by ALOX5 genotype.